1999
DOI: 10.1101/lm.6.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Labile, and Protein Synthesis– Independent Short-Term Memory in Conditioned Taste Aversion

Abstract: Short-term memory is a rapid, labile, and protein-synthesis-independent phase of memory. The existence of short-term memory in conditioned taste aversion (CTA) learning has not been demonstrated formally. To determine the earliest time at which a CTA is expressed, we measured intraoral intake of sucrose at 15 min, 1 hr, 6 hr, or 48 h after contingent pairing of an intraoral infusion of 5% sucrose (6.6 ml over 6 min) and toxic lithium chloride injection (76 mg/kg). Rats were implanted with intraoral catheters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…Eckel and Ossenkopp (1996) observed increased aversive responses 10 min after LiCl injection in intact rats. Houpt and Berlin (1999) showed that rats decreased intraoral sucrose intake 15 min after contingent pairing of intraoral sucrose and intraperitoneal LiCl. The present study reduces the time to observe CTA formation to less than 9 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eckel and Ossenkopp (1996) observed increased aversive responses 10 min after LiCl injection in intact rats. Houpt and Berlin (1999) showed that rats decreased intraoral sucrose intake 15 min after contingent pairing of intraoral sucrose and intraperitoneal LiCl. The present study reduces the time to observe CTA formation to less than 9 min.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that Eckel and Ossenkopp (1996), Houpt andBerlin (1999), andSpector et al (1988) failed to observe unconditioned effects of LiCl on intake or taste reactivity responses when rats were first tested 15 or 20 min after LiCl injection. Consistent with this finding, we observed no shifts in the ILI distribution during T2 water licking after T1 LiCl in Experiment 2, as we did for LiCl and NaCl CTA conditions in both experiments.…”
Section: Dissociation Of Associative and Unconditioned Effects Of Lic...mentioning
confidence: 99%
“…To evaluate whether the nature of the structures engaged in CTA acquisition depends on the aversion strength, we therefore studied the relationship between Fos expression levels in strong versus weak CTA conditioning. For this purpose, we used injections of different LiCl doses during CTA acquisition, because a weak malaise induces a weak CTA, whereas a strong malaise induces a strong CTA (Houpt & Berlin, 1999; Miranda et al, 2002; Nachman & Ashe, 1973; Sakai & Yamamoto, 1997).…”
mentioning
confidence: 99%
“…It has been demonstrated that CTAs are formed rapidly following the pairing of the CS with the US. A LiCl CTA is expressed 15 minutes following the pairing of saccharin with the agent (Houpt & Berlin, 1999). If this holds true for estradiol as well, then in order for estradiol to condition on the basis of satiety, the animals must be in a state of satiation shortly following the estradiol injection.…”
Section: Discussionmentioning
confidence: 99%
“…However, administration of a US after a certain interval fails to result in CTA. For instance, CS-US intervals greater than 12 hours do not support radiation CTAs (Smith & Roll, 1967) and a 24-hour inter-stimulus interval prevents acquisition of a LiCl CTA (Houpt & Berlin, 1999).…”
Section: Methodsmentioning
confidence: 99%